Here's the question you clicked on:

55 members online
  • 0 replying
  • 0 viewing

Meli36

  • 3 years ago

Solve the system. y = -1/3 x + 2 and x + 3y = 3 (0, 1) (1, 0) (3, 1/3) (3/2, 0) no solution

  • This Question is Closed
  1. goformit100
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 1

    no solution Simple Its because solve the equations or Put the Values in it ...

  2. viniterranova
    • 3 years ago
    Best Response
    You've already chosen the best response.
    Medals 0

    Making x=-3y+3 and plugging the first equation of the system. y=-1/3(3-3y)+2 y=-1+y+2; y-y=-1+2; 0=1. This is false.

  3. Not the answer you are looking for?
    Search for more explanations.

    • Attachments:

Ask your own question

Sign Up
Find more explanations on OpenStudy
Privacy Policy